Fikcja jako „dybuk” - Marek Kaźmierczak (Ksiegarnia Akademicka Publishing, 2021)
Fiction as a „dybbuk”. Remarks about the „Adherence” of the Past to the Present in the Context of the Film Titled Demon Directed by Marcin Wrona